Fermentability of Concentrated Sulfuric acid Hydrolyzates from Aspenwood and Pinewood - Janga, Kando K.; Dyrse, Nils; Øyaas, Karin; Moe, Størker T. (Tanzania Journal of Engineering and Technology, 2021)
The fermentability of hydrolyzates derived from two-stage concentrated sulfuric acid hydrolysis of Trembling aspen (Populus tremula) and Scots pine (Pinus sylvestris) were investigated. Three types of hydrolyzates were produced at mild, moderate and high decrystallization severity conditions. Portions of each of the original hydrolyzates were concentrated by vacuum evaporation to increase the sugar fraction to simulate industrial applications. Both sets of hydrolyzates were fermented anaerobically using Saccharomyces cerevisiae ATCC 96581. After 23 hours of fermentation, complete glucose consumption was observed for all the original hydrolyzates, with no signs of inhibition. The ethanol yields from these hydrolyzates ranged from 68% to 90% of theoretical value. Fermentation of concentrated aspen hydrolyzates produced at mild or moderate decrystallization severity showed a significant lag phase, associated with relatively high furfural content in the samples (approximately 2 g/L). No lag phase was apparent for aspen produced at high decrystallization severity or pine hydrolyzates. However, furfural had no adverse effect on the maximum ethanol yield. No inhibitory effect of HMF, acetic acid, formic acid or levulinic acid was detected in the concentrated hydrolyzates due to the relatively low concentrations of these compounds. The ethanol yields from concentrated hydrolyzates were above 97% of theoretical with exception of pine hydrolyzate produced at high severity which had a fairy good yield of 87%. The quantitative analysis of inhibitors and the fermentability investigation showed that both the original and concentrated hydrolyzates from the concentrated sulfuric acid process were readily fermentable, and furfural was singled out as the most important inhibitor in these hydrolyzates. Keywords: Decrystallization; trembling aspen (Populus tremula); scots pine (Pinus sylvestris); concentrated sulfuric acid; hydrolyzate; fermentability; fermentation inhibitors.